Fatores determinantes na formação da remuneração de debêntures emitidas no mercado de capitais brasileiro: governança corporativa e características da emissão - Leite, Humberto de Souza (2014)
The current scenario of the brazilian capital market shows a level of unprecedented development, showing a significant amount of the bonds issued in order to raise funds by issuing companies. The adoption of good corporate governance becomes more necessary, considering the characteristics of the investor capitas market. The present study therefore aimed to investigate the influence of adopting good corporate governance practices and some features of the debentures issued in the brazilian capital market in the formation of its yield, having specific goals to demonstrate adherence to the different levels of BOVESPA corporate governance by the issuers of debentures, describe the main features of the debentures - issue amount, term, collateral - study object, through its distribution and frequency and, finally, to identify the relationship between the yield of debentures and the condition of adhering to different levels of corporate governance BOVESPA, as well as some of their characteristics of the issue - issue amount, term and collateral - describing what impact each exercise separately on title yield. Therefore, the study sample gathers 556 debentures issued during the period from 2009 to 2012 by 350 brazilian companies. Of quantitative, descriptive research uses the techniques of descriptive statistics, simple and multiple linear regression, weighted mean difference Mann - Whitney and Kruskal - Wallis and Spearman correlation. The study results demonstrate that the issue amount has high explanatory power for the interest of the debentures. In turn, no evidence can be inferred about the influence of the term e collateral in the remuneration of roles. It was found that corporate governance measured by the adherence to the different levels of governance in BOVESPA, explains only the yield based on the Interbank Deposit (DI) plus spread, not showing the same result for other types of remuneration - percentage DI and the National Consumer Price Index (IPCA) plus spread.